Effects of Canned Pineapple Consumption on Nutritional Status, Immunomodulation, and Physical Health of Selected School Children. (20th November 2014) - Cervo, Mavil May C.; Llido, Luisito O.; Barrios, Erniel B.; Panlasigui, Leonora N.
Abstract : This randomized, controlled trial examined the effects of canned pineapple consumption on immunomodulation, nutritional status, and physical health of ninety-eight (98) school children with mean age of8.44 ± 0.20 . The study participants were divided into three groups: Group A (33) includes subjects who were not given canned pineapple, Group B (33) includes those who were given 140 g, and Group C (32) includes those given 280 g of canned pineapple for nine weeks. Each major group was further divided into two groups: normal (N) and underweight (U) based on 2007 WHO Growth Reference Standards. Sociodemographic, anthropometric, physical examination, dietary intake, hemoglobin level, and immunological data were analyzed. Results showed a decrease in incidence of viral and bacterial infections for both Group B and Group C (normal and underweight) after canned pineapple consumption. Granulocyte production increased by 0.77–26.61% for normal weight subjects and 14.95–34.55% for underweight. CD16+56 count augmented by 20.44–22.13% for normal weight and 3.57–15.89% for underweight subjects. Thus, intake of both one can (140 g) and two cans (280 g) of canned pineapple may shorten the duration and incidence of infection and may increase the production of granulocytes and CD16+56, but intake of two cans (280 g) demonstrated higher granulocyte and CD16+56 production. This trial is registered with Philippine Health Research Registry:PHRR140826-000225 .